Controlador não-linear para veículo aéreo não tripulado - Lisboa, Leandro Pfuller (2014)
With the popularization of the use of Unmanned Aerial Vehicles (UAV s) grows the need to use more sophisticated, robust and effective controllers in order to enhance its flight performance. This work aims the development of a non-linear control to be applied on a quadrotor aircraft, reducing flight time and improving system stability. The most commonly control technique used consist of a linear control law known as Proportional Integrate Derivative (PID), which provides stability and displacement for this class of system. However, this technique has certain limitations in performance by not considering construction parameters such as actuator s saturation and inertial moments, associated with the mass distribution of the system. Given this scenario, it is proposed the implementation of a control law, based on a formulation of optimal response time named Proximate Time Optimal Servomechanism (PTOS) to be applied on the degrees of freedom for rotation and translation of the vehicle. Furthermore, it is proposed a new approach to operate on a bidirectional displacement of a geo-referenced trajectory control system, based on the concept of optimal time, such as PTOS. Firstly it is presented the system dynamics, then a linearization, for purpose of control design, is achieved so that the proposed controllers are developed.